An experimental compression test of lubricants with direct measurement of lubricant pressure build-up - Sulaiman, Mohd Hafis; Christiansen, Peter Leth; Bay, Niels (Malaysian Tribology Society, 2019)
The influence of workpiece surface topography on friction, lubrication and final surface quality in metal forming operations is well known. This is especially the case when liquid lubricants are applied in situations where increased workpiece surface roughness facilitates the lubricant entrapment, pressurization and possible escape by Micro-Plasto-HydroDynamic Lubrication (MPHDL). In order to model this lubrication mechanism, an important lubricant property designated the bulk modulus is needed for characterizing the compressibility and the pressurization of the lubricant. This paper presents an experimental of direct measurement of the lubricant bulk modulus at pressure levels up to 500 MPa. The paper includes the design concept of the high-pressure equipment for the test as well as the experimental results. The bulk modulus of water as a test fluid was compared with literature values for validation of the equipment. Testing of different liquid lubricants for metal forming revealed a nonlinear relationship between the bulk modulus and the pressure.